2004
DOI: 10.1016/j.febslet.2004.08.088
|View full text |Cite
|
Sign up to set email alerts
|

Signal transduction mechanism of the seabream growth hormone secretagogue receptor

Abstract: We have recently cloned the full-length cDNAs of the two growth hormone secretagogue receptor (GHSR) subtypes from a teleost species, the black seabream (Acanthopagrus schlegeli) [Mol. Cell. Endocrinol. 214 (2004) ] i ), whereas sbGHSR-1b appeared to play an inhibitory role on the signal transduction activity of sbGHSR-1a. In the present study, we have further investigated the signal transduction mechanism of sbGHSR-1a. The peptide GHS GHRP-6 and the non-peptide GHS L163,540 were able to trigger a receptor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 52 publications
0
20
0
1
Order By: Relevance
“…The effect of ghrelin was abolished by a GHS-R antagonist, ]-GHRP-6, which is known to inhibit signal transduction mechanism also in fish GHS-R (Chan et al 2004). Those facts suggest that ghrelin activates trout phagocytes through a GHS-Rmediated mechanism.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The effect of ghrelin was abolished by a GHS-R antagonist, ]-GHRP-6, which is known to inhibit signal transduction mechanism also in fish GHS-R (Chan et al 2004). Those facts suggest that ghrelin activates trout phagocytes through a GHS-Rmediated mechanism.…”
Section: Discussionmentioning
confidence: 87%
“…A similar isoform of ghrelin is also present in rat and man as des-Gln 14 -ghrelin, which is also a ligand for GHS-R (Hosoda et al 2000(Hosoda et al , 2003. Signal transduction mediated by G protein has been detailed also in fish GHS-R (Chan et al 2004). Carboxyl-terminus is amidated in teleost ghrelins, but not in tetrapod ghrelins (Kaiya et al 2003a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently been described in two variants of GHSR1a in zebrafish (Danio rerio; Kaiya et al 2008, Olsson et al 2008, catfish, and rainbow trout (O. mykiss; Kaiya et al 2009a,b,c). Moreover, it is reported that the peptide [D-Lys 3 ]-GHRP6 inhibits the mechanism of signal transduction of synthetic GHSs (Chan et al 2004, Moulin et al 2007. Leukocytes isolated from tilapia anterior kidney were treated with the specific antagonist secretagogue receptor [D-Lys 3 ]-GHRP6 and subsequently stimulated with peptide A233.…”
Section: Discussionmentioning
confidence: 99%
“…However, the cognate GHSR has not been cloned and characterized from those fish species in which their ghrelins have been isolated or studied. To date, fish GHSR has only been reported in two species, the pufferfish Spheroides nephelus (Palyha et al 2000) and the black seabream Acanthopagrus schlegeli , and is functionally characterized in black seabream only , Chan et al 2004b. The putative ghrelin gene present in pufferfish, however, has not yet been isolated.…”
Section: Introductionmentioning
confidence: 99%